3D finite element modelling of corrosion of lap splice joints in concrete. (30th April 2018) - Abdelatif, Amged O.; Ožbolt, Joško; Gambarelli, Serena
Highlights: 3D Chemo-Hygro-Thermo-Mechanical model simulated corrosion inlap splice in concrete. The crack propagation for different corrosion levels at the joint are shown. Current density, rustproduct, rust expansion, concrete stresses are illustrated. Cathode location affectsrust distribution, mechanical and non-mechanical properties. The model shows ability to replicate the corrosion induced cracking in concrete. Abstract: The paper presents a numerical study of the chloride induced corrosion process in lap splice joints in concrete. The problem is simulated using a recently developed 3D Chemo-Hygro-Thermo-Mechanical (CHTM) model for concrete, which is employed to simulate accelerated corrosion, the same as performed in the experimental test taken from the literature. For different corrosion levels, corrosion current density, rust production, expansion of corrosion products, stresses induced in concrete and corrosion induced damage of concrete are calculated. The corrosion induced cracking of concrete cover is compared with the experimental results and good agreement between experimental observations and numerical simulations is obtained.